Partisipasi Masyarakat dalam Pembentukan Undang-undang: Studi terhadap Partisipasi Masyarakat Secara Substansial/Bermakna (Miningful Participation) - Ramadoni Ramadoni; Suryadin Suryadin; Mustamin Mustamin; Erham Erham (LPPM Institut Pendidikan Nusantara Global, 2025)
Meaningful participation has emerged as a central normative requirement in modern constitutional democracies, emphasizing that public involvement in lawmaking must extend beyond procedural formality to exert substantive influence on both legislative processes and outcomes. This study aims to examine the conceptual foundations, normative framework, and practical implementation of meaningful participation in the formation of laws in Indonesia. Employing a juridical-normative research design reinforced by empirical case analysis, the study analyzes statutory regulations, constitutional principles, and landmark decisions of the Constitutional Court, particularly those addressing legislative openness and public participation. The research further incorporates policy analysis and limited empirical observations to assess how participatory mechanisms function in practice. The findings demonstrate that although Indonesian positive law formally recognizes public participation, its implementation remains largely procedural and symbolic. Significant gaps persist between normative standards and legislative practices, including restricted access to draft laws, inadequate deliberation periods, limited representativeness of affected groups, and the absence of institutionalized feedback mechanisms. The study confirms that meaningful participation, as articulated in legal doctrine and Constitutional Court jurisprudence, consists of three core elements: the right to be heard, the right to have opinions genuinely considered, and the right to receive reasoned explanations. However, structural weaknesses, political dominance, and technical limitations continue to undermine these standards. To address these challenges, the study proposes an operational framework for meaningful participation encompassing access and inclusiveness, transparency of information, substantive influence, deliberative quality, and accountability through feedback mechanisms.